Identification of minimum essential therapeutic mixtures from cannabis plant extracts by screening in cell and animal models of Parkinson’s disease - Morash, Michael G.; Nixon, Jessica; Shimoda, Lori M. N.; Turner, Helen; Stokes, Alexander J.; Small-Howard, Andrea L.; Ellis, Lee D. (Frontiers in Pharmacology, 2022)
Medicinal Cannabis has shown promise for the symptomatic treatment of Parkinson’s disease (PD), but patient exposure to whole plant mixtures may be undesirable due to concerns around safety, consistency, regulatory issues, and psychoactivity. Identification of a subset of components responsible for the potential therapeutic effects within Cannabis represents a direct path forward for the generation of anti-PD drugs. Using an in silico database, literature reviews, and cell based assays, GB Sciences previously identified and patented a subset of five cannabinoids and five terpenes that could potentially recapitulate the anti-PD attributes of Cannabis. While this work represents a critical step towards harnessing the anti-PD capabilities of Cannabis, polypharmaceutical drugs of this complexity may not be feasible as therapeutics. In this paper, we utilize a reductionist approach to identify a minimal essential mixture of these components that are amenable to pharmacological formulation. In the first phase, cell-based models revealed that the cannabinoids had the most significant positive effects on neuroprotection and dopamine secretion. We then evaluated the ability of combinations of these cannabinoids to ameliorate a 6-hydroxydopmamine (OHDA)-induced change in locomotion in larval zebrafish, which has become a well-established PD disease model. Equimolar mixtures that each contained three cannabinoids were able to significantly reverse the OHDA mediated changes in locomotion and other advanced metrics of behavior. Additional screening of sixty-three variations of the original cannabinoid mixtures identified five highly efficacious mixtures that outperformed the original equimolar cannabinoid MEMs and represent the most attractive candidates for therapeutic development. This work highlights the strength of the reductionist approach for the development of ratio-controlled, Cannabis mixture-based therapeutics for the treatment of Parkinson’s disease.